2013
DOI: 10.3389/fgene.2013.00109
|View full text |Cite
|
Sign up to set email alerts
|

The role of endoplasmic reticulum stress in maintaining and targeting multiple myeloma: a double-edged sword of adaptation and apoptosis

Abstract: Increased cellular protein production places stress on the endoplasmic reticulum (ER), because many of the nascent proteins pass through the ER for folding and trafficking. Accumulation of misfolded proteins in the ER triggers the activation of three well-known pathways including IRE1 (inositol requiring kinase 1), ATF6 (activating transcription factor 6), and PERK (double stranded RNA-activated protein kinase-like ER kinase). The activity of each sensor modulates the overall ER strategy for managing protein q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 72 publications
(94 reference statements)
2
47
0
1
Order By: Relevance
“…[28][29][30][31] The importance of the PERK-activating transcription factor 4-CHOP arm of the UPR as a potential indicator of caspase-dependent apoptosis highlights a paradoxical aspect of the role of the UPR in plasma cell biology. 32 In this report, knockdown of IgL production and accumulation of unpaired intracellular IgH activate the UPR and ERAD in plasma cells making intact immunoglobulins but not in plasma cells making only IgL. Of note, the loss of IgH production with manufacture of only IgL and the possible toxicity of IgH to plasma cells are fundamental themes in plasma cell biology.…”
Section: Discussionmentioning
confidence: 77%
“…[28][29][30][31] The importance of the PERK-activating transcription factor 4-CHOP arm of the UPR as a potential indicator of caspase-dependent apoptosis highlights a paradoxical aspect of the role of the UPR in plasma cell biology. 32 In this report, knockdown of IgL production and accumulation of unpaired intracellular IgH activate the UPR and ERAD in plasma cells making intact immunoglobulins but not in plasma cells making only IgL. Of note, the loss of IgH production with manufacture of only IgL and the possible toxicity of IgH to plasma cells are fundamental themes in plasma cell biology.…”
Section: Discussionmentioning
confidence: 77%
“…Not surprisingly, it was found that gp96 is required for the pathogenesis of myeloma in a mouse model of disease that was driven by overexpression of the spliced variant of X-box binding protein 1 (XBP1s) [115]. Mechanistically, it was shown that gp96 chaperones Wnt signaling co-receptor LRP6, which ensures the long-term survival of myeloma cells by activating downstream target genes including survivin [145]. Thus, the dependence on gp96 to survive might be the ‘Achilles heel’ of myeloma, laying a strong foundation for development of gp96-based inhibitors against this currently incurable disease.…”
Section: Role Of Gp96 In Cancermentioning
confidence: 99%
“…The ER is an organelle that is essential for cell function and survival. Interfering with ER function activates the unfolded protein response (UPR), known as the ER stress response, which is a signal to recover ER function (Ma and Hendershot, 2004;Zhang and Kaufman, 2006;Rasheva and Domingos, 2009;White-Gilbertson et al, 2013). During ER stress, multiple signaling pathways are activated, including double-stranded RNA-activated protein kinase (PKR), the PKR-like ER kinase (PERK) and eukaryotic translation initiation factor 2 alpha (eIF2α), which suppress protein synthesis (Prostko et al, 1993;Teske et al, 2011).…”
Section: Introductionmentioning
confidence: 99%